The Role of Entrepreneurship in Enhancing Economic Development: A Literature Review on the Dynamic Interaction between Education and Human Resources - Muhtar; Dahri, Muh Ilhamuddin; Amory, Jeffriansyah Dwi Sahputra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Economic development is a crucial aspect of a country's growth and progress. The role of entrepreneurship has increasingly been recognized as a key factor in accelerating economic development. This research aims to analyze the dynamic interaction between entrepreneurship, education, and human resources in the context of economic development. This study is a qualitative literature review. Data for this literature review will be obtained through searching relevant scholarly articles and conference papers from the Google Scholar database. The search will be limited to the time span between 2010 and 2024 to ensure the freshness and relevance of information. Keywords used entrepreneurship, economic development, education, human resources. The results of the study indicate that entrepreneurship is not only a driver of economic development but also a pathway to achieving inclusive, sustainable, and beneficial economic growth for society as a whole. Thus, a holistic approach involving education, human resource development, and appropriate policy support is needed to enhance the role of entrepreneurship in economic development. Governments, educational institutions, the private sector, and society as a whole need to collaborate to create an environment that supports entrepreneurial growth and minimizes barriers to the success of new businesses